2016
DOI: 10.1111/joor.12457
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporomandibular disorders and pain in other regions of the body

Abstract: The pain from temporomandibular disorder (TMD) is often associated with physical symptoms of other chronic pain disorders and comorbidities, such as generalised muscle and joint pain. However, this association is not widely studied. To evaluate the prevalence of comorbid pain in joints, specifically in the knees, hips, ankles, shoulders, wrists and elbows, in individuals with and without TMD. We evaluated 337 patients from a public hospital in the city of Rio de Janeiro, Brazil. The Research Diagnostic Criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
(20 reference statements)
0
27
0
4
Order By: Relevance
“…Since these proteins are encoded by the DRD2 and ANKK1 genes, both are strong candidates to be studied in situations in which stress, anxiety, and pain are present. In addition, TMD is frequently associated with other painful conditions in other regions of the body . Furthermore, our previous study found association between anxiety and TMD in this same population of adolescents; therefore, DRD2 and ANKK1 were chosen as candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Since these proteins are encoded by the DRD2 and ANKK1 genes, both are strong candidates to be studied in situations in which stress, anxiety, and pain are present. In addition, TMD is frequently associated with other painful conditions in other regions of the body . Furthermore, our previous study found association between anxiety and TMD in this same population of adolescents; therefore, DRD2 and ANKK1 were chosen as candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the fact that the chief complaints of OD patients are related to occlusal somatic symptoms, they may be expressed as the somatic discomfort in whole body. Recent studies found that TMD [55] and OFP [56,57] patients experienced somatic spreading of pain symptoms in congruence with their psychiatric state progression. From these findings [55][56][57], one could suggest that symptoms in OD patients spread throughout the body depending on somatization severity.…”
Section: Discussionmentioning
confidence: 99%
“… An association between polymorphisms in the genes of estrogen receptors and the presence of temporomandibular disorders and chronic arthralgia (Quinelato et al., ). Association between Haplotypes of the RANK and OPG genes with chronic arthralgia in individuals with and without temporomandibular disorders (Bonato, Quinelato, Borojevic, et al., ; Bonato, Quinelato, De Felipe Cordeiro, et al., ). Association between ESRRB polymorphisms with comorbidity of temporomandibular disorders and rotator cuff disease (Bonato et al., ). …”
Section: Temporomandibular Disorder (Tmd)mentioning
confidence: 99%
“…Temporomandibular disorders (TMD) are characterized by painful and/or dysfunctional changes involving the masticatory muscles and temporomandibular joints (TMJ) (Bender, 2014), and collectively, they are considered the most common cause of chronic pain in the orofacial region. According to the National Institute of Dental and Craniofacial Research (NIDCR), 5%-12% of the US population suffer or have suffered from problems related to TMD (Bonato, Quinelato, Borojevic, et al, 2017;Bonato, Quinelato, De Felipe Cordeiro, et al, 2017).…”
Section: Disorder (Tmd)mentioning
confidence: 99%
See 1 more Smart Citation